Des armes en temps de paix? La dissuasion nucléaire et la menace soviétique dans le cadre d’analyse de la guerre juste des évêques catholiques américains - Epp, Roger (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1988)
Since the U.S. Catholic bishops gave their "strictly conditioned" moral acceptance of nuclear deterrence in 1983, much has changed on the strategic landscape, most notably with the emergence of numerous space-based and defensive schemes, and it is not clear how a committee struck by the hierarchy to review recent developments will respond. There are reasons to suggest the outcome will not be a complete condemnation of deterrence, whatever judgment is mode of current U.S. policies. It is equally likely that the review will fail, as did the 1983 letter, to provide sufficient justification for what it conditionally accepts. The 1983 letter cannot be construed as "soft" on the Soviet Union. But Us scant account of an expansionist adversary appears only after its moral judgments and prudential alternatives are stated. The letter, argued in a just war framework, cannot find the language to refer to a particular adversary by name or indicate why deterrence is justified on an interim basis. This f allure is ascribed to two factors. First, Catholic teaching increasingly has restricted the scope of jus ad bellum and shifted its emphasis to jus in bello criteria of discrimination and proportionality in judging modem war. Second, within a generation, the U.S. hierarchy has redefined its relationship to its society and become less willing to alter Church teaching to accomodate national purposes, even while affirming in general terms the traditional right and duty of self-defence. Y et insofar as this right remains operative, the bishops' inability to describe what is to be defended, and from what, leaves the reader unclear as to why the U.S. and its allies should possess nuclear weapons even, or only, conditionally.